The effect of external debt on economic growth in Sub-Saharan Africa - Bernardin Senadza; Agbemavor Korsi Fiagbe; Peter Quartey (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2018)
Purpose: This paper examines the effect of external debt on economic growth in Sub-Saharan Africa (SSA) in view of an upsurge in the level of external debt in many countries on the continent. Design/methodology/approach: The paper uses annual data for 39 SSA countries from 1990 to 2013 and employs the System Generalised Methods of Moments (GMM) estimation technique. Findings: The paper finds that external debt negatively affects economic growth in SSA. Categorization of countries based on per capita income however does not affect the external debt-growth nexus, neither does there exist a non-linear relationship between external debt and economic growth. Research limitations/implications: The finding of a negative relationship between external debt and growth does not necessarily imply that SSA countries should cut back on foreign borrowing in other to boost growth. Rather, given the huge savings gaps in some of the countries, what governments in SSA must do is to ensure that the foreign loans are invested in projects that would eventually generate enough returns to amortize the debt. Originality/value: Not only does the present paper extend to more recent data but we also apply one of the frontier econometric techniques - the system GMM approach - to unravel the external debt-economic growth dynamics in SSA.
Keywords: F34; O4; O47; 330; Economic Growth; External Debt; Debt Burden; System GMM; Sub-Saharan Africa